Brain tumor initiating cells: with great technology will come greater understanding. (December 2017) - Kameda-Smith, Michelle M; Manoranjan, Branavan; Bakhshinyan, David; Adile, Ashley A; Venugopal, Chitra; Singh, Sheila K
The discovery of the brain tumor initiating cells resulted in a paradigm shift within the cancer research community to consider brain tumors as an outcome of developmental mechanisms gone awry. This review will guide the reader through the technological advances that hold the powerful potential to allow brain cancer researchers to develop an intimate understanding of the dynamic and complex mechanism governing brain tumor behavior.